A influência conservadora e empresarial na perpetuação da dualidade educacional no século XXI: o processo de implementação da reforma do ensino médio no estado de São Paulo - Castilho, Bianca Bardi (2021)
The research analyses the new high school educational policy approved by the Provisal Measure n. 746/2016 and passed into the Law n. 13.415/2017. The objective of the study was to identify the implementation process of the High School Reform in São Paulo through the context of intensification of the neoliberalism and the push of conservative and corporate movements in the education. The research problem was to discuss how the High School Reform will be implemented in São Paulo in a context of political and economical crisis. The hypothesis was that, after the new curricular organization and the changes in academic load, the high school tends to strengthen the duality and inequality in the educational processes once it shapes the student for the job market in a precarious and excluding way. This research also argues that the new education proposal besides to perpetuate the historical division between humanist education and professional education can foster ranking inside on the state system. This study applied as methodology the dialectic materialism considering the relevance on the process of investigation to the object of research and the articulation of theory with the reality to understand the determiners. The theorical instruments were the bibliographic and documental analysis. The research showed that the application of the new high school system in São Paulo occurs through the development of three important projects: Currículo Paulista, Inova Educação and Novotec. The projects have the goal of articulating the curriculum of high school to the orientations of the Base Nacional Comum Curricular, separating the general formation and the professional education, adjusting the academic load, and emphasizing the curricular components to the socioemotional formation. These programs demonstrate the adequation process of the educational system to the neoliberal demands and the adherence to the work organization with basis in flexible accumulation.